Therapeutic benefits from a poorly absorbed prednisolone enema in distal colitis. Issue 8 (August 1985) - McIntyre, P B; Macrae, F A; Berghouse, L; English, J; Lennard-Jones, J E
Abstract : A double blind controlled trial has been conducted in 40 patients to compare the therapeutic effects of prednisolone metasulphobenzoate enemas with those of prednisolone-21-phosphate enemas. Both enemas brought about improvement in symptoms and sigmoidoscopic appearances in more than 70% of patients treated. The absorption of prednisolone from the metasulphobenzoate enema in three patients was less than from the 21-phosphate enema. In view of the low plasma prednisolone concentrations obtained, there are theoretical advantages in using a poorly absorbed enema to avoid the possibility of systemic steroid effects in patients requiring long term steroid treatment.